Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/1934578x1601101040
|View full text |Cite
|
Sign up to set email alerts
|

An Interesting Tour of New Research Results on Umami and Umami Compounds

Abstract: Knowledge about the fifth basic taste, the umami taste, has been investigated by many scientists in the last years and continues to gain importance. Therefore, a lot of scientific studies were conducted to explore several effects influencing the mechanism of umami, which is elicited and enhanced by defined concentrations of MSG (monosodium glutamate) and umami compounds. This paper covers the most relevant scientific literature regarding umami, its use as a flavor enhancer, and the latest umami compounds, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
(179 reference statements)
0
2
0
Order By: Relevance
“…Edible seaweeds have been widely consumed for several centuries, not only because of their availability but also because of their nutritional benefits. This tradition was maintained in Eastern culture, but the same has not occurred in the Western world Mouritsen and Styrbaek, 2014;Greisinger et al, 2016;Palmieri et al, 2020;Pérez-Lloréns et al, 2020).…”
Section: Discovery Of the Umami Taste And Its Stimuli In Edible Seaweedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Edible seaweeds have been widely consumed for several centuries, not only because of their availability but also because of their nutritional benefits. This tradition was maintained in Eastern culture, but the same has not occurred in the Western world Mouritsen and Styrbaek, 2014;Greisinger et al, 2016;Palmieri et al, 2020;Pérez-Lloréns et al, 2020).…”
Section: Discovery Of the Umami Taste And Its Stimuli In Edible Seaweedsmentioning
confidence: 99%
“…In 2005, it was shown that a stronger umami taste, up to eight times, can be obtained if all components (NEAA + 5 ′ -nucleotides) are included together, while when used separately their taste is very weak (Marcus, 2005). Nevertheless, IMP is predominately found in animal products (e.g., chicken, pork beef, tuna), and GMP is mainly found in mushrooms (Ninomiya, 1998;Yamagauchi et al, 2000;Hajeb and Jinap, 2015;Kurihara, 2009Kurihara, , 2015Greisinger et al, 2016).…”
Section: Introductionmentioning
confidence: 99%